The acute effect of erythropoietin on glucose levels during ischemia reperfusion injury in rats - Tsompos, Constantinos; Panoulis, Constantinos; Toutouzas, Konstantinos; Zografos, George; Papalois, Apostolos (Folia Medica Indonesiana, 2017)
The aim of this experimental study was to examine the effect of erythropoietin on rat model and particularly in an ischemia reperfusion (HR) protocol. The effect of that molecule was studied biochemically using blood mean glucose (Gl) levels. Materials and methods: 40 rats of mean weight 247.7 g were used in the study. Gl levels were measured at 60 min (groups A and C) and at 120 min (groups B and D) of reperfusion. Erythropoietin was administered only in groups C and D. Results were that Epo administration non-significantly increased the gl levels by 5.59% +6.46% (p=0.3208). Reperfusion time non-significantly increased the gl levels by 5.63%+6.45% (p=0.4098). However, erythropoietin administration and reperfusion time together produced a non significant combined effect in increasing the gl levels by 4.94%+3.81% (p= 0.1892). Conclusions: Results of this study indicate that erythropoietin administration, reperfusion time, or their interaction non-significantly increase the blood glucose levels in short-term. Opposite bibliographic data are considered more reliable, until a greater sample provide clearer results.